Androecia in two Clusia species: development, structure and resin secretion - Sa-Haiad, B.; Silva, C. P.; Paula, R. C. V.; Rocha, J. F.; Machado, S. R. [UNESP] (Wiley-Blackwell, 2015)
Clusia fluminensis and C.lanceolata are dioecious shrubs having resiniferous flowers with strongly distinct androecia. The aim of this study was to investigate the development and anatomy of their androecia and the ultrastructure, histochemistry and secretory process of their androecium resin glands, examining whether the cellular aspects of resin secretion differed between these two morphologically distinct androecia. Stamens differ, being free in C.fluminensis and clustered in a synandrium in C.lanceolata. Staminode sterility is due to the undifferentiated nature of the anthers in C.lanceolata and degeneration of meiocytes and anther indehiscence in C.fluminensis. Resin is produced in subepidermal cavities and canals with wide lumens. In the secretory stage, epithelial cells present sinuous walls, voluminous nuclei, polymorphic plastids associated with periplastidial reticulum, mitochondria, oil bodies, multivesicular bodies, endoplasmic reticulum and dictyosomes. The resin is released through rupture points on the distal surface of stamens and staminodes, associated with disrupted cavities and canals. Our results show morphological diversity associated with functional similarity. Also, a secretion pattern shared by the two species includes initiation of the secretory process in young floral buds, compartmentalisation of the secretion in pre-anthesis buds and release of secretions at anthesis. Cellular aspects of resin secretion in these species are quite similar, as are the chemical identities of the main components of the floral resins of the genus.
Keywords: Anatomy; Development; Flower; Resin; Secretion; Ultrastructure